Determinants of Banten Young People's Intention to Pay Waqf Through Digital Platforms - Mohamad Ainun Najib; Yayat Sujatna (Journal of Islamic Economics and Finance Studies)
The potential for cash waqf in Banten reaches IDR 55 billion per month or IDR 667.2 billion per year, but the realization is still far from expectations. One of the factors is related to the low literacy of the community, especially generation Y and Z about waqf. In a survey conducted by the Indonesian Waqf Board, the waqf literacy index score of Banten province in 2020 was 45.47 and the Waqf Basic Understanding Index Score was 50.88, this figure is in the low category. This study aims to determine the factors that influence the intention of Banten young people to donate through digital platforms, by adopting the concept of the Theory of Planned Behavior (TPB) which consists of subjective norms, perceived behavioral control, behavioral attitudes plus reliability and their influence on the intention to donate. This study uses an associative quantitative approach, the analysis was carried out using Structural Equation Modeling (SEM) with the SmartPLS application tool to test seven hypotheses of the relationship between variables in the model. Respondents, as many as 124 people were selected through a purposive sampling technique to get Muslim respondents interested in waqf through digital platforms. The results showed that subjective norms do not have a positive effect on behavioral intentions, perceived behavioral control has a positive and significant effect on behavior intention, religiosity has a significant positive effect on behavioral intention, attitude has a significant positive effect on behavioral intention. This study implies the need to improve their understanding through more intensive education and counseling, and the use of digital platforms that can facilitate access, transparency, and trust, developing and promoting digital platforms that are easily accessible, user-friendly, and secure. a more personalized approach in waqf campaigns, which emphasizes the religious aspects and direct benefits of waqf itself, to encourage waqf intentions.